The Black women first initiative: using implementation science to examine bundled interventions to improve care and treatment coordination for Black women with HIV - Serena Rajabiun; Corliss Heath; Angela Wangari Walter; Judith C. Scott; Alicia Downes; Esther Jennings; Howard J. Cabral; Cecilia Flores-Rodriguez; Linda Sprague Martinez (BMC, 2023)
Abstract Background Black cisgender and transgender women are disproportionately affected by the HIV epidemic compared to women of other racial and ethnic identities. Twelve demonstration sites across the United States are adapting, implementing and evaluating a comprehensive bundle of two or more evidence informed interventions to improve health and outcomes and quality of life for Black women with HIV. Methods Guided by Greenhalgh's Conceptual Model of Diffusion of Innovations in Health Service Organizations and Proctor's model for use of implementation strategies and evaluating implementation, service and client outcomes, this mixed methods study documents outcomes at the client, organization, and system level. Participant eligibility for the bundled interventions includes: individuals who are 18 years or older, identify as Black or African-American, identify as cisgender or transgender female and have a diagnosis of HIV. Qualitative data are collected systematically through a series of annual site visits and a standardized monthly call form to assess the barriers and facilitators to the implementation process and the key determinants impacting the intervention uptake and implementation strategies. Quantitative data collection for the implementation, service and client outcomes is conducted through a pre-post prospective study to examine the impact on Black women's health and well-being. Implementation outcomes include: the reach to Black women with HIV, adoption of interventions across the sites and their community; the fidelity to the components of the bundled interventions; the costs of the intervention; and the sustainability of the intervention in the organization and community. Primary service and client outcomes are improved linkage to and retention in HIV care and treatment, increased and sustained viral suppression, improved quality of life and resilience, and stigma reduction. Discussion The study protocol presented is specifically designed to advance the evidence for adopting culturally responsive and relevant care into clinic and public health settings to improve the health and well-being for Black women with HIV. In addition the study may advance the implementation science field by furthering what is known about the ways in which bundled interventions can address barriers to care and facilitate the uptake of organizational practices to improve health.